Solitons in normal Fermi liquid - Peradze, G.M.; Tsintsadze, N.L. (Физика низких температур, 2019)
To be based on the new quantum kinetic equation of Fermi particles, which recently was derived by N.L. Tsintsadze and L.N. Tsintsadze, a general quantum dispersion equation for almost ideal Fermi gas is derived and studied for some interesting cases. Here we consider only pair interactions between particles and we used energy expression derived by V.M. Galitski in the ordinary perturbation theory, which involves only the scattering amplitude. New effect that we have shown is that novel quantum term (Madelung term) in the kinetic equation leads to the formation of rarefaction solitary waves in neutral Fermi liquid. Furthermore, attraction and repulsion between particles have tendency to change rarefaction solitary wave speed and shape: Attraction between particles increases rarefaction soliton speed and amplitude, repulsion decreases soliton speed and amplitude. На підставі нового квантового кінетичного рівняння фермічастинок, нещодавно отриманого Н.Л. Цинцадзе та Л.Н. Цинцадзе, загальне квантове дисперсійне рівняння для майже ідеального фермі-газу вивчено для деяких цікавих випадків. Розглянуто тільки парні взаємодії між частинками та використано
вираз для енергії, отриманий В.М. Галицьким у звичайній
теорії збурень, яка включає тільки амплітуду розсіювання.
Отриманий ефект полягає в тому, що новий квантовий член
(терм Маделунга) в кінетичному рівнянні призводить до утворення розріджених відокремлених хвиль в нейтральній фермірідині. Більш того, притягання та відштовхування між частинками мають тенденцію до зміни швидкості й форми таких
хвиль: притягання між частинками збільшує швидкість та амплітуду солітону, а відштовхування зменшує швидкість та
амплітуду солітону. На основании нового квантового кинетического уравнения
ферми-частиц, недавно полученного Н.Л. Цинцадзе и Л.Н.
Цинцадзе, общее квантовое дисперсионное уравнение для
почти идеального ферми-газа изучено для некоторых интересных случаев. Рассмотрены только парные взаимодействия
между частицами и использовано выражение для энергии,
полученное В.М. Галицким в обычной теории возмущений,
которая включает только амплитуду рассеяния. Полученный
эффект заключается в том, что новый квантовый член (терм
Маделунга) в кинетическом уравнении приводит к образованию разреженных уединенных волн в нейтральной фермижидкости. Более того, притяжение и отталкивание между частицами имеют тенденцию к изменению скорости и формы
таких волн: притяжение между частицами увеличивает скорость и амплитуду солитона, а отталкивание уменьшает скорость и амплитуду солитона.